La construction « trine » de la sexualité de l’enfant classé déficient intellectuel : perspective parentale: The "trine" construction of the sexuality of the child classified as intellectually disabled: parental perspective - Desjardins, Michel (Revue francophone de la déficience intellectuelle, 2009)
Les parents se font couramment reprocher d’infantiliser leur enfant classé déficient intellectuel. Afin de saisir le sens, la fonction et la valeur morale de cette pratique, j’ai interviewé (en 2000) 15 parents de la région montréalaise. Les parents ont été rencontrés à trois occasions : une histoire de vie et deux entrevues semi-structurées. Ils ont narré l’histoire de la vie et du développement de leur enfant âgé de 15 à 25 ans. Le cadre théorique utilisé s’inspire de la sémiotique de la culture et de la phénoménologie critique. L’analyse des entrevues révèle que les parents décrivent leur enfant essentiellement à travers trois figures : ils lui attribuent non pas un mais trois types de sexualité. Ils l’inscrivent non pas dans un mais dans trois cycles de vie parallèles. Abstract Parents are commonly criticized for infantilizing their child who is classified as intellectually disabled. In order to understand the meaning, function and moral value of this practice, I interviewed (in 2000) 15 parents in the Montreal area. The parents were interviewed on three occasions: a life story and two semi-structured interviews. They told the story of their child's life and development between the ages of 15 and 25. The theoretical framework used is based on cultural semiotics and critical phenomenology. The analysis of the interviews reveals that the parents describe their child essentially through three figures: they attribute to him not one but three types of sexuality. They place him in not one but three parallel life cycles.